2017
DOI: 10.1177/2058460117732101
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-short echo time magnetic resonance imaging for detection of pulmonary arteriovenous malformation recanalization after coil embolization: a case report and a phantom study

Abstract: A pulmonary arteriovenous malformation (PAVM) is a direct connection between the pulmonary arteries and veins for which metallic coil transcatheter embolization is the standard of care. Detecting recanalization after PAVM treatment is crucial, but direct visualization with computed tomography or magnetic resonance imaging (MRI) is generally difficult. Here, we report a case of a recanalized PAVM that was directly detected with ultra-short echo time MRI. The detection of these signals in the coils was confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…A further clinical study among a larger number of patients with visceral arterial disease is required to evaluate the merits of noncontrast imaging techniques relative to CE imaging techniques. Second, although the usefulness of the 3D UTE technique has been previously reported in studies examining other vascular territories after endovascular treatment, further research with patients should assess its effectiveness for examining visceral arteries treated with various types of metal devices 19–22 . As the phantom and patient studies have demonstrated, the use of stainless steel‐based devices could be challenging for MRA image acquisition, despite using the 3D UTE technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A further clinical study among a larger number of patients with visceral arterial disease is required to evaluate the merits of noncontrast imaging techniques relative to CE imaging techniques. Second, although the usefulness of the 3D UTE technique has been previously reported in studies examining other vascular territories after endovascular treatment, further research with patients should assess its effectiveness for examining visceral arteries treated with various types of metal devices 19–22 . As the phantom and patient studies have demonstrated, the use of stainless steel‐based devices could be challenging for MRA image acquisition, despite using the 3D UTE technique.…”
Section: Discussionmentioning
confidence: 99%
“…In the head and neck region, 3D UTE‐MRA allows clear visualization of parent arteries after coil embolization and stent placement, in contrast to the conventional time‐of‐flight MRA 19–21 . In pulmonary MRA, 3D UTE‐MRA also permits the assessment of pulmonary arteriovenous fistula recanalization 22 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the utility of UTE MRI in the detection of PAVM recanalization has been reported. 14 This method visualizes the continuity through the embolized coils from the feeding artery to the draining vein, but physicians might misinterpret static tissues, including thrombi in coils and sacs as lesions, given their high signal intensity. Therefore, imaging modalities that provide hemodynamic information in addition to UTE MRI remain necessary to evaluate recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…With 3D radial MRA, for instance, the UTE is obtained by applying a short duration, spatially nonselective hard pulse for RF excitation, simultaneous gradient ramping and data acquisition, and sampling with half radial projections. Potential benefits of UTE MRA include reduction of flow artifacts related to rapid, turbulent flow and off‐resonance artifacts from metallic implants . Another virtue of certain UTE MRA techniques like PETRA is that the magnetic field gradients are much less active than with standard MRA techniques, which decreases acoustic noise and results in a so‐called “silent” scan …”
Section: New Developmentsmentioning
confidence: 99%